Proyecto control fiebre aftosa Sabana de Bogotá, Valles de Ubaté y Chiquinquirá. - Robles Rojas, Luis Alberto; Cediel S., Jairo; Sánchez L ., Hugo; Matallana, Germán Darío; Reyes, Juan; López C., Miguel Ángel (Instituto Colombiano Agropecuario, 1986)
Ganadería bovina